Identifying the Factors Influencing Information Usefulness and Information Adoption in Promoting Organ Donation through Social Media - Faerozh Madli; Sharifah Nurafizah Syed Annuar; Stephen Laison Sondoh Jr; Andreas Totu (2018)
The effectiveness of social media in the context of organ donation is uncertain because of the mixed findings reported in the literature. Hence, this paper aims to review the literature and to identify the factors in social media that can influence one’s decision to register as an organ donor. Most of the earlier studies focused on examining the attitude and knowledge of people toward organ donation after an exposure to social media. However, not many studies look into the impact of message framing towards adoption of information through social media platform. Review from the past studies reveals that information quality, information credibility, visual information, and accessibility information are the possible predictors towards information usefulness in the context organ donation. In the meantime, we propose that information usefulness to have a positive association towards information adoption which will lead to the intention to register as organ donors. A research model is proposed in this study which includes all the variables that are discussed in this paper.